KOMUNIKASI PEMASARAN USAHA KULINER DI KOTA PEKANBARU - Oktri Permata Lani; Ilham Havifi (Alfuad: Jurnal Sosial Keagamaan, 2018)
The city of Pekanbaru is a strategic area where the population is increasing and becoming a metropolitan city. The rapid development of Pekanbaru City is also reflected in the rapid growth of businesses in various places, with various business sectors. One of the most prominent efforts is the business in the culinary field. Almost in every corner of the culinary business available in the city of Pekanbaru with a variety of culinary choices. The great desire of culinary entrepreneurs in the city of Pekanbaru in carrying out their business, maintaining, developing to become bigger and then reaching the peak. In this case, three culinary ventures in Pekanbaru, namely Martabak Djoeragan, Mini Chef and Waroenk Baper, require marketing communication in the introduction of their culinary business to the community, not only as an introduction but also to maintain the existence of their business. This study uses quality methods. The results of this study indicate that the clinical marketing communication of the clinicians in Pekanbaru Kta through advertising activities, sales promotion activities, public relations and public relations activities, personal sales activities, direct marketing activities, event activities and experiences. Besides marketing communication is also associated with brand equity, which is seen from brand awareness and response to the brand. The use of New Media is very important in maintaining, introducing, and developing its business.